60-year Anniversary of the International Law Commission - A. H. Abashidze; A. M. Solntsev (Московский журнал международного права)
In the year of 2008 the 60th anniversary session of International Law Commission took place and the article is devoted to this subject. The author conducts a full-scale description of the history of the work of the International Law Commission highlighting major points of its activities and expressing his own opinions. For example, the author states that if the topic “independence of states” had been codified it could have been possible to avoid several international problems as in the case with the situation in Kosovo.Further on the author dwells on the subject of Soviet and later on Russian representatives participation in the work of International Law Commission.As for the anniversary meeting there were discussed 8 topics, which are enumerated and discussed in the article.Upon the whole the International Law Commission greatly contributed and continues to do so in the spheres of the law of the sea, international criminal law, law of the treaties and other spheres. In detail the author touches upon the role of International Law Commission in the development of international ecological law and the elaboration of the notion of “soft law”. The author also pays attention to the relations between International Law Commission and the International Court of justice and comes to the conclusion that their relations can be characterized as symbiosis.In the conclusion the author states that International Law Commission accomplishes very difficult but necessary work and expresses the opinion that there will be new achievements in the process of codification and the progressive development of the international law.